Hydrogen bonding and rate enhancement in the photoinduced polymerization of telechelic urethane methacrylates based on a cycloaliphatic system: tricyclodecane dimethanol - Deepak, V. D.; Rajan, J.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
A new class of telechelic urethane methacrylic crosslinkers, based on a cycloaliphatic system (tricyclodecane dimethanol and tricyclodecane monomethanol), was synthesized. The synthesis was achieved by a two-step condensation of 1,6-hexamethylene diisocyanate or isophorone diisocyanate with tricyclodecane dimethanol and capping with hydroxyethyl methacrylate. Samples of hexanediol diacrylate, tricyclodecane monomethacrylate, and tricyclodecane dimethacrylate were used as non-hydrogen-bonding monomers for comparative studies of the curing kinetics. The photopolymerization of these telechelic systems was investigated with UV irradiation in the presence of 2,2-diethoxy acetophenone as the photoinitiator, and the kinetics were followed by the monitoring of the double-bond conversion at 815 cm−1 with Fourier transform infrared spectroscopy. The hydrogen-bonded crosslinkers had higher double-bond conversions than their non-hydrogen-bonded counterparts under identical conditions. The higher cure rate could be explained by hydrogen-bonding preassociation in these systems, which brought the methacrylate double bonds within close proximity. The temperature effects on the hydrogen bonding were also investigated. A decrease in the extent of the double-bond conversion with increasing temperature was observed for the hydrogen-bonded crosslinker, in contrast to an increased conversion with temperature for hexanediol diacrylate and tricyclodecane dimethacrylate. This was directly indicative of a reduction of hydrogen bonding at elevated temperatures leading to lower conversions. © 2006 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 44: 4384–4395, 2006